PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP PERTANGGUNGJAWABAN ANGGARAN PENDAPATAN BELANJA DESA (APBDes) - T. Putri Nabila; Andi Afrizal (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
The purpose of this research was to determine the Effect of Accountability and Transparency on Accountability of Village Expenditure Budget (APBDes) in the Village Office of North Central Rambah, Rokan Hulu Regency, this research used descriptive and quantitative methods using data analysis of respondents' achievement levels (TCR) with the analysis model multiple linear regression obtained from the results of Y = 23.695 + 0, 418 X1 + 0.796 X2 + e. Data obtained through structured interviews with respondents is the apparatus of the North Central Rambah Village. The results of this research indicate that Accountability and Transparency has a positive effect on the Village Expenditure Budget. With a value of 51.7% influenced by Accountability and Transparency and the rest 48.3% is influenced by other variables outside this research.